2020
DOI: 10.1186/s12889-020-8409-2
|View full text |Cite
|
Sign up to set email alerts
|

The association between PM2.5 exposure and suicidal ideation: a prefectural panel study

Abstract: Background: Suicidal ideation is subject to serious underestimation among existing public health studies. While numerous factors have been recognized in affecting suicidal thoughts and behaviors (STB), the associated environmental risks have been poorly understood. Foremost among the various environment risks were air pollution, in particular, the PM2.5. The present study attempted to examine the relationship between PM 2.5 level and local weekly index of suicidal ideation (ISI). Methods: Using Internet search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 92 publications
(74 reference statements)
1
9
0
Order By: Relevance
“…In our study, we found a positive correlation between HLSA and PM 2.5 . Recently, several studies confirmed our findings, reporting short-and long-term effects of higher levels of PM 2.5 and PM 10 on suicidal behaviors, including attempted and completed suicides (36)(37)(38)(39)(40)(41)(42)(43)(44). However, the concentration and composition of air pollutants and population-level features (i.e., age and race) vary across countries.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, we found a positive correlation between HLSA and PM 2.5 . Recently, several studies confirmed our findings, reporting short-and long-term effects of higher levels of PM 2.5 and PM 10 on suicidal behaviors, including attempted and completed suicides (36)(37)(38)(39)(40)(41)(42)(43)(44). However, the concentration and composition of air pollutants and population-level features (i.e., age and race) vary across countries.…”
Section: Discussionsupporting
confidence: 86%
“…For example, Bernardini et al (35) considered daily admissions to psychiatric emergency services in two Italian hospitals over a period of 2 years and highlighted that exposures to ozone may be associated with increased psychiatric admissions. Recently, several studies reported that higher levels of particulate matters (PM 2.5 and PM 10 ) were linked to an increase in suicidal behaviors (attempts and deaths) worldwide (36)(37)(38)(39)(40)(41)(42)(43)(44), demonstrating both short-and long-term effects. Nevertheless, other studies report the absence of this association (34,45).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Third, the infrastructure for public health communications could be less developed in the developing countries. 20,21 Information insufficiency, especially paucity of updated information verified by public health authorities, may lead the healthcare workers in less developed countries or regions to believe in misinformation. 22 In other words, even if some healthcare workers are not prone to misinformation, there are delays and geographic disparities in receiving and absorbing accurate health information.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the serious effects of haze pollution on public health, most studies have focused on the analysis of public health and air pollution. In contrast, few studies examine the relationship from the perspectives of both management and economics (Chen et al, 2020;Qu & Yan, 2015). In response to China's emerging environmental and public health problems, the attention of medical scholars has been drawn to the effects of environmental pollution on public health.…”
Section: Literature Reviewmentioning
confidence: 99%